Lung Cancer Screening at a Military Treatment Facility: A Retrospective Review. Issue 5 (11th January 2020) - White, Lindsey J; Kaur, Antarpreet; Lapel, Raechel T; E Boswell, Gilbert; Luceri, Robert E; Parrish, John Scott; Seda, Gilbert
Abstract: Introduction: Lung cancer is the leading cause of cancer death among men and women, accounting for more fatalities than colon, breast, and prostate cancers combined. Smoking causes about 85% of all lung cancers in the United States and is the single greatest risk factor. In 2013, the US Preventive Services Task Force (USPSTF) published initial guidelines for low-dose computed tomography lung cancer screening (LCS) among patients 55–80 years old, with a 30-pack-year history, who are current smokers or who quit within the previous 15 years. Smoking prevalence is higher among military personnel compared to the civilian population, demonstrating a need for vigilant screening. Materials and Methods: A retrospective review of Naval Medical Center San Diego's (NMCSD) LCS data was conducted to examine screening numbers, lung cancer rates, and initial analysis of screening results. Patients were referred for screening if they met the USPSTF criteria. Between September 2013 and September 2018, 962 patients underwent LCS. A total of 1758 examinations were performed, including follow-up and annual surveillance examinations. The American College of Radiology's Lung CT Screening Reporting and Data System (Lung-RADS) was used to classify lung nodules' risk for malignancy. Results: On this initial analysis, 42 enrolled patients received the diagnosis of lung cancer detected by screening. The initial calculated lung cancer rate is 4.4% (42/962) over the 5-year reporting period. The lung cancer rate among those patients with a Lung-RADS score of 3 or 4 was 31% (42/135). Thirty-seven patients were classified as having non-small cell lung cancer (NSCLC), while five were classified as having small cell lung cancer. Of the 37 NSCLC patients, 76% (28/37) were diagnosed at stage I and II, 11% (4/37) were diagnosed at stage III, and 13% (5/37) were diagnosed at stage IV. The total number of years a person smoked was a significant risk factor ( P  = 0.004), but not pack-years a person smoked ( P  = 0.052). Conclusions: These preliminary results demonstrate the success of a Military Treatment Facility (MTF)-based LCS Program in the detection of early stage lung cancer. Earlier stage detection may result in better health outcomes for affected patients. In the population studied, duration of smoking proved to be more significant than pack-years in predicting lung cancer risk. These results validate the newly dedicated resources and continued efforts to strengthen the LCS program at NMCSD and across MTFs.